2019
DOI: 10.1007/s40618-019-01111-9
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly and ultrasound: how, when and why?

Abstract: Background Acromegaly is a rare disease caused by an excess of growth hormone and insulin-like growth factor 1. It is usually diagnosed because of typical signs such as macroglossia, acral enlargement, jaw prognathism and malocclusion. Systemic complications are a major cause of morbidity and mortality in acromegaly, and many patients remain undiagnosed for several years. Increased ultrasound (US) application in the general population, and including among acromegaly patients, has revealed many suggestive featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…The findings for IHD, 9 osteoarthritis, 12 colon polyps, 14,15 and uterine fibroids 49 are in line with some of the available prospective or genetic evidence from population-based studies, and the results for kidney stones are supported by studies in adults with acromegaly. 5 It is possible that some of these associations were masked by reverse causality in the first five years of follow-up, and follow-up with larger numbers is needed to clarify whether IGF-I might associate with these outcomes. This is the first study to adopt an outcome-wide approach to the investigation of IGF-I and risk of 25 common conditions (other than cancer); this comprehensive approach allowed us to assess and compare the effect sizes of multiple outcomes within the UK Biobank and reduce outcome-selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings for IHD, 9 osteoarthritis, 12 colon polyps, 14,15 and uterine fibroids 49 are in line with some of the available prospective or genetic evidence from population-based studies, and the results for kidney stones are supported by studies in adults with acromegaly. 5 It is possible that some of these associations were masked by reverse causality in the first five years of follow-up, and follow-up with larger numbers is needed to clarify whether IGF-I might associate with these outcomes. This is the first study to adopt an outcome-wide approach to the investigation of IGF-I and risk of 25 common conditions (other than cancer); this comprehensive approach allowed us to assess and compare the effect sizes of multiple outcomes within the UK Biobank and reduce outcome-selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…kidney stones, enlarged prostate 4 ), respiratory disease, sleep apnoea, and some cancers. 5,6 Higher IGF-I concentrations in adults without acromegaly have been shown to also be associated with increased risks of several cancers, 7 but corresponding evidence for noncancer outcomes is inconsistent and/or limited to cross-sectional design. Although some of the available prospective observational and genetic evidence suggests that higher IGF-I levels might be positively associated with type 2 diabetes, 8,9 ischaemic heart disease (IHD), [9][10][11] hip and knee osteoarthritis, 12 enlarged prostate, 13 and colon adenomas, 14,15 some studies also reported null, [16][17][18][19][20][21][22][23][24] and inverse 25 associations for these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, BPH is reported in approximately half the acromegalic subjects 65,67 and the prevalence of parenchymal alterations (ie, cysts, calcifications and nodules) is also increased 65,66,68 . Slight increase in PSA levels and International Prostate Symptom Scores (IPSS) are also reported in these patients, although prostatic symptoms are often absent 67,69 . Moreover, as results from a large population study, prostatic cancer (PCa) incidence is increased both in healthy individuals with IGF‐I levels in the upper reference range 70,71 and in acromegalic patients 72 .…”
Section: Physiology Of Crosstalk: the Chicken And The Eggmentioning
confidence: 99%
“…65,66,68 Slight increase in PSA levels and International Prostate Symptom Scores (IPSS) are also reported in these patients, although prostatic symptoms are often absent. 67,69 Moreover, as results from a large population study, prostatic cancer (PCa) incidence is increased both in healthy individuals with IGF-I levels in the upper reference range 70,71 and in acromegalic patients. 72 However, a recent meta-analysis of 23 studies in acromegaly reveals some potential sources of bias in the association between acromegaly and PCa: for example, cancer incidence was more pronounced in smaller and single-center studies (selection bias) and the enlarged PV in acromegaly may lead to more frequent US examination (diagnostic workup bias).…”
Section: How the Extratesticular Effects Of Gh And Igf-i Impact Thementioning
confidence: 99%
“…carpal tunnel syndrome), genitourinary diseases (e.g. kidney stones, enlarged prostate [4]), respiratory disease, sleep apnoea, and some cancers [5,6].…”
Section: Introductionmentioning
confidence: 99%